Development Strategies for Grid-Connected Utility-Scale Solar Photovoltaic to Increase Renewable Energy Penetration - Budi Ariyadi, Surya; Purwanto, Widodo W (CSID Journal of Infrastructure Development, 2024)
The government of Indonesia has launched programs to decarbonize its power systems by replacing fossil fuel-based plants with renewable energy. Solar photovoltaic (PV) deployment faces economic and technical barriers despite abundant solar irradiance. This study evaluates techno-economic strategies for 10 MW grid-connected solar PV systems, comparing two scenarios: without Battery Energy Storage System (BESS) and with BESS to reduce grid reliance. Key interventions were analyzed for their economic impacts, including tariff adjustments, carbon tax implementation, and competitive auction schemes. The results show that without BESS, the project achieves an Internal Rate of Return (IRR) of 21.30%, making it highly feasible. However, including BESS lowers the IRR to 5.89% due to higher costs. Combining carbon tax and tariff adjustments improves feasibility, achieving a Profitability Index (PI) of 1.00 and an IRR of 14.74%. Competitive auctions further lower costs, enhancing the feasibility of BESS projects. While solar PV without BESS is economically viable, risks of capital cost increases require attention. For BESS projects, policy interventions such as auctions and incentives are essential. This study highlights strategic measures to accelerate solar PV adoption in Indonesia, providing insights for policymakers and investors to scale up renewable energy deployment effectively.